Sympathetic dysregulation induced by postnatal intermittent hypoxia - Karlen-Amarante, Marlusa [UNESP] (2023)
Study Objectives Exposure to postnatal chronic intermittent hypoxia (pCIH), as experienced in sleep-disordered breathing, is a risk factor for developing cardiorespiratory diseases in adulthood. pCIH causes respiratory instability and motor dysfunction that persist until adult life. In this study, we investigated the impact of pCIH on the sympathetic control of arterial pressure in rats. Methods and Results Neonate male Holtzman rats (P0-1) were exposed to pCIH (6% O-2 for 30 seconds, every 10 minutes, 8 h/day) during their first 10-15 days of life, while control animals were maintained under normoxia. In early adult life (P25-40), freely behaving pCIH animals (n = 13) showed higher baseline arterial pressure levels linked to augmented sympathetic-mediated variability than control animals (n = 12, p < 0.05). Using decerebrated in situ preparations, we found that juvenile pCIH rats exhibited a twofold increase in thoracic sympathetic nerve activity (n = 14) and elevated firing frequency of ventromedullary presympathetic neurons (n = 7) compared to control rats (n = 6-7, p < 0.05). This pCIH-induced sympathetic dysregulation was associated with increased HIF-1 alpha (hypoxia-inducible factor 1 alpha) mRNA expression in catecholaminergic presympathetic neurons (n = 5, p < 0.05). At older age (P90-99), pCIH rats displayed higher arterial pressure levels and larger depressor responses to ganglionic blockade (n = 6-8, p < 0.05), confirming the sympathetic overactivity state. Conclusions pCIH facilitates the vasoconstrictor sympathetic drive by mechanisms associated with enhanced firing activity and HIF-1 alpha expression in ventromedullary presympathetic neurons. This excessive sympathetic activity persists until adulthood resulting in high blood pressure levels and variability, which contribute to developing cardiovascular diseases.